A pilot evaluation of respiratory mechanics during prehospital manual ventilation. (August 2022) - Yang, Betty Y.; Blackwood, Jennifer E.; Shin, Jenny; Guan, Sally; Gao, Mengqi; Jorgenson, Dawn B.; Boehl, James E.; Sayre, Michael R.; Kudenchuk, Peter J.; Rea, Thomas D.; Kwok, Heemun; Johnson, Nicholas J.
Abstract: Introduction: Respiratory mechanics, such as tidal volume (VT ) and inspiratory pressures, may affect outcome in hospitalized patients with respiratory failure. Little is known about respiratory mechanics in the prehospital setting. Methods: In this prospective, pilot investigation of patients receiving prehospital advanced airway placement, paramedics applied a device to measure respiratory mechanics. We evaluated tidal volume (VT ) per predicted body weight (VT PBW) to determine the proportion of breaths within the lung-protective range of 4–10 mL/kg per PBW overall, according to ventilation bag volume (large versus small) and cardiac arrest status (active CPR, post-ROSC, non-arrest). Results: Over 16-months, 7371 post-intubation breaths were measured in 54 patients, 32 patients with cardiac arrest and 22 with other conditions. Paramedics ventilated 19 patients with a small bag and 35 patients with a large bag. Overall, mean VT was 435 mL (95% CI 403, 467); VT PBW was 7.0 mL/kg (95% CI 6.4, 7.6) with 75% within the lung-protective range. Mean VT PBW and peak pressure differed according to arrest status (absolute difference −0.36 mL/kg and 32 cmH2 O for active CPR compared to post-ROSC), though not according to bag size. Conclusions: We observed that measuring respiratory mechanics in the prehospital setting was feasible. Tidal volumes were generally delivered within a safe range. Respiratory mechanics varied most significantly with active CPR with lower VT PBW and higher peak pressures, though did not seem to be affected by bag size. Future work might examine the relationship between respiratory mechanics and outcomes, which may identify opportunities to improve clinical outcomes.